Mobile-phone application with zoonotic disease information for smallholder farmers in East Africa - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
This partnership commenced in April 2017. Between then and November 2019, a total of 178,000 sms texts have been received by 12,643 smallholder farmers, primarily in Kenya. The most requested information has been on anthrax, brucellosis, Rift Valley fever, foot and mouth disease and leptospirosis.